Transitional justice and redress for racial injustices against marginalized minorities: lessons from indigenous Twa people in post-genocide Rwanda - Sentama, Ezechiel (International journal of transitional justice, 2024)
This article addresses the question of how countries respond to racial injustices through transitional justice. It draws on the case of Rwanda and explores the experiences of the marginalized indigenous Twa minorities with transitional justice implemented after the 1994 genocide through the National Unity and Reconciliation Commission and Gacaca courts. The lessons from Rwanda highlight the limitations of transitional justice in providing redress for racial injustices of marginalized minorities when it is practised within an authoritarian political context. The article discusses how the transitional justice approach in Rwanda contributed to the construction of a flawed record of the past and marginalized the racial realities of Rwandans by imposing an official historical narrative. It was also used as a tool of the government to negate racial injustices against the most marginalized communities of Twa people but also to preserve racial injustices and human rights violations against them by denying their ethnic identity and indigenous way of life.